Ecological correlates of chital (Axis axis) reproductive seasonality in Kanha Tiger Reserve - Shravana Goswami; Ujjwal Kumar; Qamar Qureshi; Yadvendradev Jhala (Scientific Reports)
Abstract Reproductive seasonality in mammals is often influenced by top down and bottom up effect. While tropical and equatorial regions exhibit continual breeding due to stable resources, tropical India experiences pronounced seasonality in forage availability. This study investigates the breeding timing of chital (Axis axis) in the tropical deciduous forests of Central India at Kanha Tiger Reserve, where forage availability varies seasonally. Field observations focused on antler conditions in males and lactation signs in females to estimate breeding timing. Rutting peak, as determined by males with hard antlers, coincided with nutritional peak induced by the monsoon, which probably was also the cue for ovulation in females. Lactation, the most nutritionally demanding period, peaked with the post-fire sprouting of herbaceous vegetation in April and fawn weaning synchronized with ample food availability. This synchrony between reproductive cycles and forage availability emphasizes the adaptive strategies of chital to maximize offspring survival. Furthermore, the peak in tiger births coincided with the fawning peak of chital, making them vulnerable prey during a nutritionally demanding period for tigresses, who are restricted in their movements near vulnerable cubs. Understanding the links between trophic levels and their seasonality offers important insights for wildlife management and conservation strategies.